Modern contraceptive utilization among female ART attendees in health facilities of Gimbie town, West Ethiopia - Polisi, Addisu (BioMed Central, 2014)
BACKGROUND: In many areas of the world where HIV prevalence is high, rates of unintended pregnancy have also been shown to be high. Of all pregnancies worldwide in 2008, 41% were reported as unintended and approximately 50% of these ended in abortion. To address these problems family planning is the best solution. Therefore, the purpose of the study was to assess modern contraceptive use among females on ART in health facilities of Gimbie town, Western Ethiopia. METHODS: A facility based cross-sectional study was conducted in Gimbie town, western Ethiopia from December 2012 to January 2013. HIV infected women of reproductive age group (15-49 years) who came for ART care follow up during the data collection period were included in the study. Data was collected using an interviewer administered questionnaire. Binary logistic regression and multivariate analysis were employed using SPSS version 17. RESULTS: Three hundred ninety five women on ART have participated in the study. More than half, 224 (56.7%), of the respondents were using modern contraceptive, of whom 67 (30%) use dual contraceptive method. Having information on modern contraception is positively associated with modern contraceptive use with (AOR=6.3, 95% CI (1.67, 24.1)) and respondents who have family size ≤4 were 50% less contraceptive users than those who have family size >4 (AOR=0.51, 95% CI (0.27, 0.96)). CONCLUSION: In this study contraceptive use among HIV positive women is better than the general population. However, use of dual methods, long acting and permanent method of contraceptives were found to be low. Continuous and targeted information provision on modern contraceptive should be done.